Performing financial communication as professional practice: The interplay of consensus and tension in earnings calls - Hirsto, Heidi; Koskela, Merja; Jokipii, Annukka (Oxford University Press, 2023)
Financial communication is a form of organizational communication that links strategic and managerial views on the firm with the surveilling gaze of investors and the financial market, thereby functioning as a practice of transparency. In this article, we focus on the interaction between corporate managers and market analysts in an institutionalized, professional genre of financial communication: the earnings call. Our goal is to increase understanding of how the earnings call as a public and interactional genre contributes to the enactment and constitution of financial communication as a professional practice. We conduct a close analysis of four earnings calls, combining a term-based analysis of the conceptual structuring of the calls with a discourse–rhetorical analysis of manager–analyst interaction. The analysis shows how communication of consensus, based on evoking a common body of expertise, alternates with expressions of potential tension in ways that have complex and contradictory effects on transparency. While the evocation of expertise signals common ground and boundaries around the professional practice, the rhetoric of tension constructs boundaries between the professional roles, producing a relation of surveillance. We consider both the ideational consensus and the role-related tension as performative achievements and constitutive elements of the earnings call. Their combination functions to perform earnings call as a site of both specialized expertise and transparency, thus lending legitimacy to financial communication as a professional practice. Through applying a communication-centered theoretical lens, the study adds to the understanding of professions as constructed in and through professional relations, and through the communicative practices that structure and stabilize these relations.
Keywords: financial communication; earnings call; professional practic; communication-centered view; tension; consensus; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Viestintätieteet|en=Communication Studies|